Implementasi Lots Dan Hots Serta Implikasi Pada Proses Pembelajaran Di Sekolah Dasar - Fitri Ramadhani; Nurfadilah; St. Khuznul khotimah; Rachmat Alim Taqwa (PT PUSTAKA CENDEKIA GROUP, 2024)
This research aims to describe the implementation of LOTS and HOTS based learning. As we already know, the independent curriculum requires implementing HOTS-based learning because HOTS learning is very important for students, especially elementary school students. This research uses a qualitative research design which aims to describe the phenomenon in depth. Meanwhile, the method used is library research. The results of the research are that Low Order Thinking Skill (LOTS) is a student's ability to think functionally. Meanwhile, Higher Order Thinking Skills (HOTS) or the ability to think critically, logically, reflectively, metacognitively, and think creatively are high level thinking abilities.